Unsupervised feature selection regression model with nonnegative sparsity constraints - Zhao, Xue; Li, Qiaoyan; Xing, Zhiwei; Dai, Xuezhen (Journal of intelligent & fuzzy systems, 2023)
Selecting appropriate features can better describe the characteristics and structure of data, which play an important role in further improving models and algorithms whether for supervised or unsupervised learning. In this paper, a new unsupervised feature selection regression model with nonnegative sparse constraints (URNS) is proposed. The algorithm combines nonnegative orthogonal constraint, L2,1-norm minimum optimization and spectral clustering. Firstly, the linear regression model between the features and the pseudo labels is given, and the indicator matrix, which describes feature weight, is subject to nonnegative and orthogonal constraints to select better features. Secondly, in order to reduce redundant and even noisy features, L2,1-norm for indicator matrix is added to the regression model for exploring the correlation between pseudo labels and features by the row sparsity property of L2,1-norm. Finally, pseudo labels of all samples are established by spectral clustering. In order to solve the regression model efficiently and simply, the method of nonnegative matrix decomposition is used and the complexity of the given algorithm is analysed. Moreover, a large number of experiments and analyses have been carried out on several public datasets to verify the superiority of the given model.